Assessment of polychlorinated biphenyls (PCBs) in the Himalayan Riverine Network of Azad Jammu and Kashmir. (February 2020) - Ullah, Rizwan; Asghar, Rehana; Baqar, Mujtaba; Mahmood, Adeel; Alamdar, Ambreen; Qadir, Abdul; Sohail, Muhammad; Schäfer, Ralf B.; Musstjab Akber Shah Eqani, Syed Ali
Abstract: The emission of polychlorinated biphenyls (PCBs) in South Asian countries is one of the great environmental concerns and has resulted in the contamination of surrounding high altitude regions such as Azad Jammu and Kashmir (AJK), Pakistan. This first investigation of Polychlorinated Biphenyl (PCBs) concentrations in the ambient air, water and surface soil was conducted along the extensive stream network in the AJK valley of the Himalayan Region. In 2014, surface soil samples were taken and passive air and water samplers were deployed along the four main rivers, namely Jhelum, Neelum, Poonch and Kunhar, and analysed for PCBs (33 congeners) using GC-MS/MS. The ∑33 PCBs concentrations ranged from 31.17 to 175.2 (mean ± SD: 81 ± 46.4 pg/L), ND to 1908 (1054 ± 588.5 pg/g), and 29.8 to 94.4 (52.9 ± 22.7 pg/m 3 ) in surface water, soil and air matrices, respectively. The levels of dioxin-like PCBs (∑8 DL-PCBs) contributed considerably towards the total PCBs concentrations: 60.63% (water), 43.87% (air) and 13.76% (soil). The log transformed air-water fugacity (log fa/fw ) ratios ranged from −9.37 to 2.58; with 86.3% of the sampling sites showing net volatilization of selected PCB congeners. Similarly, the fugacity fractions for air-soil exchange exhibited narrow variation (0.8 to < 1) indicating net volatilization of PCBs. The ecological risk assessment showed low potential ecological risks ( E r i  = 1.58–7.63) associated with PCB contamination. The present findings provide baseline data that suggest cold trapping of POPs in the remote mountainous areas of Pakistan and can support environmental management of POPs at the regional level. This pioneer investigation campaign to assess the PCBs concentrations in Himalayan Riverine Network of Azad Jammu and Kashmir, Pakistan helps to develop baseline data of PCBs from the strategically important riverine environment that would help in future regional as well as global ecological studies. However, the effects of temperature variations on the sampling rates of chemicals across a wide spectrum of volatility along the elevation gradient were not taken under consideration for PCBs atmospheric concentrations. Graphical abstract: Image 1 Highlights: Pioneer investigation of PCBs in riverine network of AJK, Pakistan. Hepta-PCBs (in water), penta-PCBs (in soil), and hexa-PCBs (in air) identified as dominant homologs. Net volatilization of PCBs from soil and water to the atmosphere. Low potential ecological risks associated with PCB contamination. Abstract : Practical Implications: